The Effect of The COVID-19 Pandemic on The Tax Compliance of Digital Economy Business - Puspitarini, Ndaru; Rahimi, Aulia (Universitas Negeri Semarang, 2023)
Purpose: Tax authority have faced one of the challenges collecting tax revenue during the Covid-19 pandemic in decreasing of the economy will potentially leads firms in financial distress. Financial distress motivated firms to engage tax avoidance. Moreover, activities in the digital economy that are growing rapidly could be a challenge to prevent tax avoidance. Thus, this research intends to investigate how the Covid-19 pandemic affects associations between businesses that engage in digital economy activities and tax avoidance on Indonesian public enterprises. Method: The study used sample of 250 firms which are listed on Indonesia Stock Exchange (BEI) in 2018-2021 and conducted using difference-in-difference method. Findings: The study finds empirical evidence that digital economy activities positively associated with effective tax rate. Nevertheless, the Covid-19 pandemic weakened this association. Novelty: Previous studies partially examined the relationship between the COVID-19 pandemic on tax avoidance and the digital economy on tax avoidance. Quantitative researches about digital business are also mainly carried out in developed countries considering that digital economic activities have been massively carried out in developed countries. This study will complement previous studies where the Covid-19 pandemic and economic activity will be interacted with and linked to corporate tax avoidance behaviour, especially in Indonesia. Keywords: Covid-19; Tax Avoidance; Digital Economy